The Development of a Web-Based Booking System for Badminton Court in Batu Pahat - Lim, Xin Woei; Darman, Rozanawati (Applied Information Technology And Computer Science, 2023)
A web-based booking system for badminton courts in Batu Pahat has been implemented to help the booking process. 10 badminton courts in Batu Pahat were included in the study. Currently, customers are required to contact the person in charge of the court or visit in person to make reservations. Additionally, badminton court owners manually record bookings, leading to a risk of overlaps. To address these issues, a web-based booking system was developed to benefit badminton court owners, customers, and system administrators. One of the badminton court owners is appointed as the system administrator. The methodology used in this project is Agile to ensure the requirements are met. There are 4 modules in the developed system, including user management, court management, court reservation, and report generating.  In general, the system performs as a portal that allows badminton court owners to rent their courts and customers to make reservations online easily.